Solid-phase-supported synthesis of morpholinoglycine oligonucleotide mimics - Tatyana V. Abramova (Beilstein Journal of Organic Chemistry, 2014)
An efficient solid-phase-supported peptide synthesis (SPPS) of morpholinoglycine oligonucleotide (MorGly) mimics has been developed. The proposed strategy includes a novel specially designed labile linker group containing the oxalyl residue and the 2-aminomethylmorpholino nucleoside analogues as first subunits.